Phyto-Engineered Gold Nanoparticles (AuNPs) with Potential Antibacterial, Antioxidant, and Wound Healing Activities Under in vitro and in vivo Conditions - Boomi P (Dove Medical Press, 2020)
Pandi Boomi,1 Ramalingam Ganesan,2 Gurumallesh Prabu Poorani,3 Sonamuthu Jegatheeswaran,4 Chandrasekaran Balakumar,5 Halliah Gurumallesh Prabu,6 Krishnan Anand,7 Narayanasamy Marimuthu Prabhu,8 Jeyaraman Jeyakanthan,1 Muthupandian Saravanan9 1Department of Bioinformatics, Alagappa University, Karaikudi, Tamil Nadu, India; 2Department of Chemistry, Arumugam Seethaiyammal Arts and Science College, Tiruppattur, Tamil Nadu, India; 3Kumaraguru College of Technology, Coimbatore, Tamil Nadu, India; 4The Key Laboratory of Advanced Textile Materials and Manufacturing Technology of Ministry of Education, College of Materials and Textile, Zhejiang Sci-Tech University, Hangzhou, People’s Republic of China; 5Faculty of Pharmacy, Philadelphia University, Amman, Jordan; 6Department of Industrial Chemistry, School of Chemical Sciences, Alagappa University, Karaikudi, Tamil Nadu, India; 7Department of Chemical Pathology, School of Pathology, Faculty of Health Sciences and National Health Laboratory Service, University of the Free State, Bloemfontein, South Africa; 8Disease Control and Prevention Lab, Department of Animal Health and Management, Science Campus, Alagappa University, Karaikudi, Tamil Nadu, India; 9Department of Medical Microbiology and Immunology, Division of Biomedical Sciences, School of Medicine, College of Health Science, Mekelle University, Mekelle, EthiopiaCorrespondence: Pandi Boomi; Muthupandian Saravanan Email pboomi1983@gmail.com; saravanan.muthupandian@mu.edu.etBackground: A diabetic ulcer is one of the major causes of illness among diabetic patients that involves severe and intractable complications associated with diabetic wounds. Hence, a suitable wound-healing agent is urgently needed at this juncture. Greener nanotechnology is a very promising and emerging technology currently employed for the development of alternative medicines. Plant-mediated synthesis of metal nanoparticles has been intensively investigated and regarded as an alternative strategy for overcoming various diseases and their secondary complications like microbial infections. Hence, we are interested in developing phyto-engineered gold nanoparticles as useful therapeutic agents for the treatment of infectious diseases and wounds effectively.Methods and Results: We have synthesized phyto-engineered gold nanoparticles from the aqueous extract of Acalypha indica and characterized using advanced bio-analytical techniques. The surface plasmon resonance feature and crystalline behavior of gold nanoparticles were revealed by ultraviolet-visible spectroscopy and X-ray diffraction, respectively. High-performance liquid chromatography analysis of the extract demonstrated the presence of different constituents, while major functional groups were interpreted by the Fourier-transform infrared spectroscopy as the various stretching vibrations appeared for important O-H (3443 cm− 1), C=O (1644 cm− 1) and C-O (1395 cm− 1) groups. Scanning electron microscopy, high-resolution transmission electron microscopy results revealed a distribution of spherical and rod-like nanostructures with 20 nm of size. The gold nanoparticle-coated cotton fabric was evaluated for the antibacterial activity against Staphylococcus epidermidis and Escherichia coli bacterial strains which revealed remarkable inhibition at the zone of inhibition of 31 mm diameter against S. epidermidis. Further, antioxidant activity was tested for their free radical scavenging property, and the maximum antioxidant activity of the extract containing gold nanoparticles was found to be 80% at 100 μg/mL. The potent free radical scavenging property of the nanoparticles is observed at IC50 value 16.25 μg/mL. Moreover, in vivo wound-healing activity was carried out using BALB/c mice model with infected diabetic wounds and observed the stained microscopic images at different time intervals (day 2, day 7 and day 15). It was noted that in 15 days, the wound area is completely re-epithelialized due to the presence of different morphologies such as spherical, needle and triangle nanoparticles. The re-epithelialization layer is fully covered by nanoparticles on the wound area and also collagen filled in the scar tissue when compared with the control group.Conclusion: The pharmacological evaluation results of the study indicated an encouraging antibacterial and antioxidant activity of the greener synthesized gold nanoparticles tethered with aqueous extract of Acalypha indica. Moreover, we demonstrated enhanced in vivo wound-healing efficiency of the synthesized gold nanoparticles through the animal model. Thus, the outcome of this work revealed that the phyto-engineered gold nanoparticles could be useful for biomedical applications, especially in the development of promising antibacterial and wound-healing agents.Keywords: gold nanoparticles, antibacterial, antioxidant, wound healing, in vivo mice model